2011
DOI: 10.1002/jrs.2665
|View full text |Cite
|
Sign up to set email alerts
|

Surface‐enhanced Raman scattering study of human serum on PVAAg nanofilm prepared by using electrostatic self‐assembly

Abstract: Polyvinyl alcohol (PVA)-protected silver nanoarchitecture (PVA-Ag nanofilm) on the surface of the glass substrate was prepared by using electrostatic self-assembly at a proper voltage. The two-dimensional morphology of the PVA-Ag nanofilm has been examined by scanning electron microscopy (SEM). The surface-enhanced Raman scattering (SERS) spectra of human serum (HS) on PVA-Ag nanofilms were recorded. The results show that the Raman scattering of HS can be enhanced efficiently based on these PVA-Ag nanofilms. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 36 publications
1
31
0
Order By: Relevance
“…1, along with their difference. Both spectra present features already reported by several groups [16,18,20,21,36], using various substrates, and in particular, the bands due to uric acid and hypoxanthine [18,19,37].…”
Section: Resultssupporting
confidence: 52%
“…1, along with their difference. Both spectra present features already reported by several groups [16,18,20,21,36], using various substrates, and in particular, the bands due to uric acid and hypoxanthine [18,19,37].…”
Section: Resultssupporting
confidence: 52%
“…3c) exhibits similar vibrational frequencies as reported for the SERS spectra of plasma due to other plasmonically enhancing substrates excited at 785 nm, including enriched Au 5 and Ag 3, 4, 6, 26 colloid solutions and a PVA-Ag nanoparticle films. 27 As seen in Fig. 3, the SERS spectrum of fresh whole blood (Fig.…”
Section: Resultsmentioning
confidence: 86%
“…It is found that there are no or weak Raman signals from sodium citrate adsorbed on the Al substrate and PVA‐Ag nanofilms prepared with the reaction time of 20 s. However, large enhancements for the Raman scattering of sodium citrate adsorbed on PVA‐Ag GPs prepared with the reaction times of 40 and 60 s are observed, indicating large Raman scattering enhancements of the PVA‐Ag GPs prepared with the reaction times of 40 and 60 s. The normal Raman spectrum of powder sodium citrate is demonstrated in Fig. S3 (Supporting Information), and the main experimental Raman and SERS wavenumbers and their assignments are displayed in Table S1 based on our previous works . To verify the reproducibility of the SERS spectra on the basis of this substrate, we performed error bars for Raman band areas at 705, 1000, 1237 and 1390 cm −1 in the SERS spectra of (b), (c) and (d) shown in Fig.…”
Section: Resultsmentioning
confidence: 99%